A biochemometric approach for the assessment of Phyllanthus emblica female fertility effects as determined via UPLC-ESI-qTOF-MS and GC-MS. Issue 8 (10th July 2019) - Khaled, Sally E.; Hashem, Fatma A.-M.; Shabana, Manal H.; Hammam, Abdel-Mohsen M.; Madboli, Abdel Nasser A.; Al-Mahdy, Dalia A.; Farag, Mohamed A.
Abstract : Phyllanthus emblica L. fruits have long been used in Ayurvedic medicine for their many health benefits. Abstract : Phyllanthus emblica L. fruits have long been used in Ayurvedic medicine for their many health benefits. In this study, we present P. emblica fruit crude extract and fractions' effects on the female reproductive system by assessing its estrogenic and gonadotropic activities. Results revealed that the non-polar petroleum ether and chloroform fractions exhibited the strongest estrogenic and follicle-stimulating hormone-like [FSH] activity, while the n -butanol fraction exhibited a significant luteinizing hormone-like [LH] activity. The ethyl acetate fraction showed neither estrogenic nor gonadotropic activities and in contrast it may impair female fertility suggesting that different metabolite classes contribute to the plant's overall effect on female fertility. To pinpoint active agents in these fractions, UPLC/ESI-qTOF-MS- was employed for secondary metabolite profiling with 100 metabolites annotated including ellagitannins, gallic acid derivatives, terpeneoids, sterols, phthalates and fatty acids. Correlation between extracts/fraction bioassays and UPLC/MS data was attempted using orthogonal partial least squares-discriminant analysis (OPLS-DA) revealing that guaiane-type sesquiterpenes, phthalates, diterpenes and oxygenated fatty acids showed positive correlation with estrogenic and gonadotropic activities. In contrast, mucic acid gallates, gallic acid derivatives and ellagitannins correlated negatively. GC/MS analysis of the non-polar bioactive fractions viz . petroleum ether and chloroform was also attempted which revealed its enrichment in fatty acids/fatty acyl esters (34%) and phenolic compounds (19.6%). This study provides the first report on the estrogenic and gonadotropic activities of P. emblica fruits in relation to their metabolite fingerprint.